Preparation method of calcined-free raw phosphogypsum-based multi-solid-waste light foamed curb stone
Patent Information
- Application Number
- CN202611272752.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-11-03
AI Technical Summary
In existing technologies, the high-value utilization of phosphogypsum is limited by the slow hydration rate and unstable strength caused by its acidic impurities. Furthermore, CO2 mineralization is limited to the surface of the material and cannot achieve internal reinforcement, making it difficult to meet the durability requirements of municipal components such as curbs.
Using uncalcined virgin phosphogypsum as the main material, combined with carbide slag activation and carbon dioxide mineralization curing, a microporous network is formed through foaming. Impurities are passivated in situ by utilizing the alkaline activation effect of carbide slag, and internal mineralization is achieved under carbon dioxide pressure to generate nano-sized calcium carbonate crystals. This solves the technical problems in the existing technology field and realizes deep mineralization enhancement and early strength improvement of the material.
It enables large-scale utilization of phosphogypsum, and the material has rapid early strength, stable physical properties, is lightweight and high-strength, and has good durability, meeting the requirements of municipal construction, reducing production energy consumption and carbon emissions, and avoiding environmental pollution risks.
Smart Images

Figure CN123026422A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of building materials and road engineering technology, specifically relating to a method for preparing a non-calcined undisturbed phosphogypsum-based lightweight foamed curbstone. Background Technology
[0002] Resource utilization of industrial solid waste is a key technological area supporting ecological civilization construction and achieving the "dual carbon" goal. Phosphogypsum's main component is calcium sulfate dihydrate, but it also contains residual free phosphoric acid, fluorides, and organic matter, among other impurities. Its acidic leaching risk and high environmental impact have led to its classification as a key controlled bulk solid waste. For a long time, phosphogypsum has primarily been disposed of through open-air stockpiling, which not only occupies significant land resources but also causes continuous pollution of surrounding soil and water bodies by heavy metal ions and acidic substances in leachate from stockpiles, posing a severe challenge to the green and sustainable development of phosphate chemical enterprises. In recent years, relevant authorities have explicitly required improving phosphogypsum disposal capacity and promoting the research and industrial application of large-scale phosphogypsum utilization technologies. The high-value and resource-based utilization of phosphogypsum has become a strategic issue that the industry urgently needs to address.
[0003] In terms of strength, phosphogypsum has a slow hydration rate, resulting in low early strength of the material. The presence of free phosphoric acid, fluoride and other organic impurities in phosphogypsum leads to unstable hydration products, which macroscopically manifests as fluctuations in later strength and low long-term durability, making it difficult to meet the durability requirements of municipal components such as curbs.
[0004] In recent years, the industry has attempted to introduce carbon dioxide (CO2) mineralization curing technology to enhance the strength of solid waste building materials. However, existing technologies suffer from a common technical bias and bottleneck: for traditional dense solid waste materials, CO2 mineralization often only reaches the surface; the calcium carbonate crystals formed on the surface quickly block the surface capillary pores, preventing CO2 gas from penetrating further into the interior. This lack of internal mineralization results in extremely limited overall strength improvement. Therefore, eliminating the negative impact of acidic impurities in phosphogypsum and achieving deep mineralization enhancement within the material without calcination is a pressing technical challenge in the field of bulk solid waste resource utilization. Summary of the Invention
[0005] This invention aims to provide a lightweight, unprocessed phosphogypsum curbstone that requires no calcination, has a high phosphogypsum content (40%~50%), exhibits rapid early strength development, and possesses stable physical properties. Through carbide slag activation and carbon dioxide (CO2) mineralization curing, harmful impurities are passivated in situ, while simultaneously improving the material's density and low-carbon properties.
[0006] A method for preparing a non-calcined undisturbed phosphogypsum-based lightweight foamed curbstone made from solid waste includes the following specific steps: Step 1: Each preset amount of solid dry material contains a preset first proportion of phosphogypsum, a preset second proportion of mineral powder, a preset third proportion of carbide slag, a preset fourth proportion of fly ash, and a preset fifth proportion of machine-made fine sand. The phosphogypsum is uncalcined virgin phosphogypsum with a moisture content controlled within a preset range; the amount of mixing water is the sixth preset proportion of the total mass of solid dry material after removing the manufactured sand; the physical foaming agent is diluted with water and pre-prepared into foam by a foaming machine, and then added according to the seventh preset proportion. Step 2: Add the phosphogypsum, mineral powder, carbide slag, fly ash and machine-made fine sand prepared in Step 1 into a mixer and mix them dry. Step 3: Add the specified amount of mixing water to the uniformly mixed solid dry material from Step 2 and perform wet mixing. Control the speed within the preset first speed range and stir for the preset first time period until a uniform gel slurry is formed. Step 4: Use a foaming machine and foaming agent to produce foam. The foaming pressure should be controlled within the preset first pressure range, the foam dry density should be controlled within the preset density range, and the bubble size should be controlled within the preset pore size range. Step 5: Add the foam prepared in Step 4 to the gelling slurry prepared in Step 3, stir at low speed until uniform, control the stirring speed within the preset second speed range, stir for the preset second time period, and then pour the foam-containing mixture into the mold. No vibration is required; it will self-compact and form. Let the formed sample stand for initial setting to form initial structural strength and lock in air bubbles. Step 6: Step-by-step curing, including placing the pre-set molded specimen in a sealed carbonization curing chamber or curing box, introducing industrial-grade carbon dioxide or pretreated industrial flue gas, ensuring the carbon dioxide volume concentration is not lower than a preset concentration threshold, and controlling the pressure within a preset second pressure range, curing for a preset second time period. During this process, carbon dioxide gas diffuses into the interior of the specimen through the microporous network formed by foaming, dissolves in the pore liquid to form carbonic acid, and reacts with hydration products and unreacted calcium hydroxide in the system to generate nano-calcium carbonate crystals, filling the pores of the hardened slurry, thereby rapidly improving the early strength of the specimen and densifying the microstructure; and after demolding, transferring the specimen to a standard curing chamber or outdoors for natural curing or periodic water spraying curing for a preset curing cycle to ensure that the hydration reaction of the internal cementitious material is fully carried out and to obtain stable final performance.
[0007] Preferably, in step 1, calcium carbide slag is used as the core activator, and its main effective component is calcium hydroxide. The quality of calcium carbide slag directly affects the in-situ passivation effect on free phosphoric acid and fluoride in phosphogypsum, as well as the degree of activation of pozzolanic activity of mineral powder and fly ash. The amount of calcium carbide slag used is controlled within the preset calcium carbide slag usage range.
[0008] Preferably, in step 1, mineral powder and fly ash are used as auxiliary cementing materials. The total mass fraction of mineral powder and fly ash is controlled within the preset auxiliary cementing material ratio range. Under the alkaline activation of carbide slag, mineral powder and fly ash undergo a pozzolanic reaction to generate hydrated calcium silicate gel, which together with the subsequently generated calcium carbonate forms a gel-microcrystalline dual network structure.
[0009] Preferably, in step 1, the machine-made fine sand is used as micro-aggregate, and the amount is controlled within the preset fine sand dosage range. Pure slurry foam is prone to cracking during hardening and shrinkage. Adding a small amount of fine sand can provide rigid support, effectively control the volume shrinkage rate of the curbstone, and reduce the generation of cracks.
[0010] Preferably, in step 3, the wet mixing speed is controlled within a preset first speed range, and the mixing time is controlled within a preset first time period. Too low a speed will result in uneven mixing, while too high a speed will easily cause the slurry temperature to rise, affecting the subsequent foaming effect. The mixing endpoint is determined by forming a uniform, lump-free gel slurry.
[0011] Preferably, in step 4, the foaming pressure is controlled within a preset first pressure range, the foaming dry density is controlled within a preset density range, and the bubble size is controlled within a preset pore size range. If the pore size is too small or the connectivity is low, the carbon dioxide gas diffusion resistance will increase sharply, making it impossible to achieve internal mineralization; if the pore size exceeds the preset upper limit of the pore size, it will damage the macroscopic load-bearing capacity of the material.
[0012] Preferably, in step 4, the physical foaming agent is an anionic surfactant-type foaming agent, which is diluted with water and then foamed by a foaming machine within a preset first pressure range. The volume of the foam accounts for a preset seventh proportion of the volume of the gel slurry. If the proportion of the foam volume is too low, the weight reduction effect will be insignificant; if the proportion is too high, the strength will be excessively reduced.
[0013] Preferably, in step 5, the low-speed stirring speed after the foam is added is controlled within a preset second speed range, and the stirring time is controlled within a preset second time period. If the stirring speed is too fast, the foam will break and be lost. If the stirring time is too short, the foam will be unevenly distributed, affecting the consistency of the pore structure of the final product.
[0014] Preferably, in step 5, after pouring into the mold, self-compacting molding is adopted, and no additional vibration is required. Vibration will cause the foam to float and break, affecting the uniformity of foam distribution. The time for initial setting is controlled within a preset third time period according to the ambient temperature, with the formation of initial structural strength and locking of air bubbles as the judgment criteria.
[0015] Preferably, in step 6, the pressure of carbon dioxide carbonization curing is controlled within a preset second pressure range, the carbon dioxide volume concentration is not lower than a preset concentration threshold, and the curing time is controlled within a preset second time period. Under this pressure condition, carbon dioxide gas can rapidly penetrate into the material through the interconnected microporous network formed by foaming, thereby achieving deep mineralization enhancement.
[0016] Preferably, in step 6, the subsequent natural curing or water spraying curing is carried out for a preset curing cycle of continuous curing. The early carbon dioxide mineralization curing mainly improves the early strength and densification of the microstructure, while the later hydration curing ensures that the hydration reaction of the internal cementitious material is fully carried out, so that the final performance is stable.
[0017] Preferably, the present invention also includes alternative solutions for the alkali activator. In addition to carbide slag, the strong alkaline environment provider in step 1 can also be replaced by one or more combinations of quicklime, steel slag powder or sodium hydroxide, as long as it can provide sufficient hydroxide ion concentration to activate the activity of mineral powder and fly ash and passivate free phosphoric acid and fluoride impurities in phosphogypsum in situ.
[0018] Preferably, the present invention also includes alternative foaming methods. In addition to physical foaming, chemical foaming can also be used, that is, hydrogen peroxide or aluminum powder is added to the dry mixture as a gas generating agent, and gas is generated in situ inside the slurry through chemical reaction to build a microporous permeable network. Chemical foaming can also achieve pore size control within a suitable range.
[0019] Preferably, the present invention also includes an alternative solution for the carbonization curing gas source. In addition to using high-purity carbon dioxide gas, the sealed carbonization gas source in step 6 can also be directly introduced into industrial waste gas, such as carbon dioxide-rich flue gas emitted by chemical plants or thermal power plants. This can not only achieve the same mineralization enhancement effect, but also further reduce costs and achieve industrial exhaust gas treatment.
[0020] Preferably, when the phosphogypsum content of the curbstone prepared by the present invention reaches the preset maximum content, its apparent density is controlled within the preset density range, achieving significant weight reduction compared to traditional concrete. However, thanks to the reinforcement of the calcium carbonate skeleton, its compressive strength at the preset test age can reach the preset strength range, fully meeting the mechanical requirements of relevant concrete curbstones.
[0021] Compared with the prior art, the present invention has the following beneficial effects: 1. No calcination and low carbon emissions: This invention uses uncalcined virgin phosphogypsum as the main substrate, eliminating the high-energy-consuming process of high-temperature calcination to prepare hemihydrate gypsum in traditional processes. The alkaline activation effect of carbide slag replaces the high-temperature activation process, which greatly reduces the energy consumption and carbon emissions in the production process.
[0022] 2. High utilization and resource utilization: This invention adopts a cement-free design, using phosphogypsum as the main material, supplemented by mineral powder, fly ash, carbide slag and machine-made fine sand and other solid wastes in synergistic effect. The phosphogypsum dosage can reach a preset high dosage, realizing the large-scale utilization of phosphogypsum.
[0023] 3. Synergistic effect of in-situ alkalization and mineralization: This invention organically couples the alkali activation effect and impurity passivation effect of carbide slag with the pressure mineralization enhancement effect of carbon dioxide. The hydroxide ions released by the dissolution of carbide slag break the glassy network of fly ash and mineral powder, stimulating their potential cementing activity. At the same time, it rapidly neutralizes the free phosphoric acid and fluoride remaining in phosphogypsum, converting them into extremely difficult-to-dissolve crystal precipitates, thereby eliminating the inhibitory effect of acidic impurities on early hydration.
[0024] 4. Pore-mineralization synergistic creation: This invention utilizes the interconnected microporous network formed by foaming under a preset foaming pressure as a diffusion channel for carbon dioxide gas permeation. This microporous network allows carbon dioxide to quickly penetrate into the core area of the curbstone and generate nano-calcium carbonate on the pore walls with calcium ions excited by carbide slag. The foamed pores are transformed from mechanical defects into mineralization microreactors, solving the industry problem that traditional dense materials are blocked by surface carbonization and cannot be mineralized internally.
[0025] 5. Deep mineralization enhancement: Under preset pressurized carbon dioxide curing conditions, carbon dioxide gas rapidly penetrates into the material through the microporous network formed by foaming, generating nano-sized calcium carbonate crystals in situ. These crystals firmly adhere to the foam pore walls, forming a dense nanocrystalline skeleton that blocks capillary leakage channels and significantly improves the early compressive strength of the material. The preset early age strength can reach a high level.
[0026] 6. Lightweight and high strength: The microporous network formed by physical foaming reduces the apparent density of the finished product to within the preset density range, achieving significant weight reduction compared to traditional concrete. This greatly reduces the difficulty of hoisting in municipal construction. At the same time, thanks to the calcium carbonate skeleton reinforcement and the gel-microcrystalline dual network structure, the pre-set compressive strength at later ages can still reach a high strength range.
[0027] 7. Durability and safety: The formation of nano-calcium carbonate crystals densifies the microstructure, improving the material's impermeability and durability. At the same time, the concentration of free phosphorus leaching can be controlled below the preset concentration limit, meeting the initial screening requirements for leaching toxicity in relevant hazardous waste identification standards, and posing no risk of secondary environmental pollution. Attached Figure Description
[0028] Figure 1 This is a system flowchart of the present invention. Detailed Implementation
[0029] Example 1: This example details a method for preparing lightweight foamed paving stones based on undisturbed phosphogypsum without calcination. This method achieves efficient resource utilization of phosphogypsum through precise raw material proportioning, optimized foaming processes, and innovative step-by-step curing technology, producing lightweight, high-strength, low-carbon, and environmentally friendly paving stone products. The method comprises six core steps: raw material proportioning, dry mixing, wet mixing and slurry preparation, physical foaming, foam slurry mixing and pouring, and step-by-step curing. These steps are closely integrated, forming a complete technical closed loop.
[0030] In step 1, the raw material weighing is performed with 100 parts by weight of solid dry material according to the following precise proportions: 40-50 parts phosphogypsum, 15-20 parts mineral powder, 3-5 parts carbide slag, 15-17 parts fly ash, and 15-20 parts manufactured fine sand. The preferred proportion in this embodiment is: 45 parts phosphogypsum, 16 parts mineral powder, 4 parts carbide slag, 15 parts fly ash, and 20 parts manufactured fine sand. This proportion was determined through extensive orthogonal experiments, comprehensively considering multiple performance indicators such as early strength, later strength, apparent density, and free phosphorus leaching concentration. As the main substrate, the amount of phosphogypsum directly determines the amount of solid waste disposed of and the contribution to the skeletal volume of the curbstone. However, excessive amounts can lead to insufficient alkalinity of the system and an exacerbated impurity inhibition effect; therefore, it is controlled within the range of 40-50 parts. Mineral powder and fly ash are used as auxiliary cementitious materials, with a combined dosage of 30-37 parts. Their synergistic effect can effectively activate the pozzolanic activity and generate hydrated calcium silicate gel to compensate for the loss of pore strength caused by foaming. Calcium carbide slag is used as the core activator, with its dosage strictly controlled at 3-5 parts. It must provide sufficient hydroxide ion concentration to activate the activity of mineral powder and fly ash, while ensuring complete neutralization of free phosphoric acid and fluoride impurities in phosphogypsum. Mechanized fine sand is used as micro-aggregate, with a dosage of 15-20 parts. Its role is to provide rigid support during the foaming, hardening, and shrinkage of the pure slurry, effectively controlling the volume shrinkage rate and reducing crack formation.
[0031] The phosphogypsum used is virgin phosphogypsum without any high-temperature calcination treatment. Its main chemical component is calcium sulfate dihydrate (CaSO4·2H2O), and it also contains residual free phosphoric acid (H3PO4), fluoride (HF), and organic matter as impurities. The moisture content of the virgin phosphogypsum must be strictly controlled between 15% and 25%. If the moisture content is too low, the phosphogypsum particles will be too dry, increasing the wetting contact angle with water, making it difficult to form an effective gelling slurry during mixing. If the moisture content is too high, it will increase the water-cement ratio, reducing the cohesiveness and air retention of the slurry, affecting the foaming effect and early strength. In this embodiment, the moisture content of the virgin phosphogypsum is controlled at 18%. At this moisture content, the surface of the phosphogypsum particles exhibits a moderately wetted state, ensuring both affinity with water and preventing excessive moisture from affecting the total solids content of the dry solids.
[0032] The amount of mixing water is 30% to 40% of the total mass of the solid dry material after removing the manufactured sand (i.e., the total mass of phosphogypsum, mineral powder, carbide slag, and fly ash). In this embodiment, the total mass of the powder after removing the manufactured fine sand is 80 parts by mass, and the amount of mixing water is 28 parts by mass, corresponding to a water-cement ratio of 0.35. This water-cement ratio has been optimized through rheological performance testing to ensure that the slurry has sufficient fluidity and self-compacting properties, while preventing foam from rising and the formation of weak interfacial zones due to bleeding.
[0033] The physical foaming agent used is an anionic surfactant-type foaming agent, which has advantages such as high foaming ratio, good foam stability, and strong compatibility with cementitious materials. After diluting the foaming agent with water according to the instructions, it is placed in a dedicated foaming machine for pre-foaming. The core component of the foaming machine is a high-speed impeller shearing device, which thoroughly mixes the liquid foaming agent with air through impeller rotation, forming a large number of uniform and fine bubble clusters. The prepared foam is added at 20% to 40% of the volume of the cementitious slurry formed after mixing with water; in this embodiment, the foam addition is 30% of the cementitious slurry volume. Too low a foam volume percentage will result in insignificant weight reduction, making it difficult to fully utilize the advantages of lightweight construction; too high a foam volume percentage will significantly reduce the solid content of the slurry, leading to excessive reduction in strength after molding.
[0034] In step 2, the phosphogypsum, mineral powder, carbide slag, fly ash, and manufactured fine sand prepared in step 1 are all added to a forced mixer for dry mixing. The purpose of dry mixing is to ensure that the solid particles achieve a uniform spatial distribution before the addition of water, creating conditions for subsequent wet mixing and hydration reactions. The dry mixing time is set to 2-3 minutes, and the rotation speed is controlled at 60-80 rpm. During the dry mixing process, the solid particles of each component are displaced, tumbled, and collided under the push of the mixing blades, and the relative positions between the particles are continuously adjusted, eventually achieving a statistically uniform distribution. No water should be added during the dry mixing stage, otherwise some phosphogypsum particles will hydrate prematurely, forming an irreversible crystalline structure, affecting the subsequent foaming effect and mechanical properties.
[0035] In step 3, the specified amount of mixing water is added to the uniformly mixed solid dry material from step 2 for wet mixing. The wet mixing speed is strictly controlled between 120 and 150 rpm, preferably 130 rpm in this embodiment. The wet mixing time is controlled between 3 and 5 minutes, 4 minutes in this embodiment. During the wet mixing process, the addition of water rapidly wets the surface of the solid particles, and the hydration reaction is initiated. Too low a speed will result in insufficient mixing intensity, uneven distribution of particles in the aqueous phase, and local agglomeration or clumping of powder; too high a speed will cause the slurry temperature to rise under the action of stirring friction, accelerating the hydration and exothermic process of carbide slag, resulting in a rapid increase in slurry consistency and affecting the subsequent foaming process. The wet mixing endpoint is the formation of a uniform, clumpy gelatinous slurry. At this point, the slurry has a creamy consistency, good thixotropy and wall adhesion, and can effectively encapsulate and stabilize air bubbles during the subsequent foaming process.
[0036] Carbide slag plays a crucial and multifaceted role in this system. Its main active component is calcium hydroxide (Ca(OH)2), with a content exceeding 80%. During the wet mixing stage, the carbide slag particles undergo a hydration reaction upon contact with water: Ca(OH)2 → Ca... 2+ +2OH - This process releases a large amount of hydroxide ions. On the one hand, it provides a strongly alkaline environment (pH value can reach above 12.5), breaking the passivation film on the surface of the mineral powder and fly ash glass, exposing the active silicon and aluminum phases, enabling them to react with calcium hydroxide in a pozzolanic reaction. On the other hand, the strongly alkaline environment can rapidly neutralize the residual free phosphoric acid and fluoride impurities in phosphogypsum, converting them into extremely difficult-to-dissolve crystalline precipitates, thereby eliminating the inhibitory effect of acidic impurities on early hydration. The passivation reaction equation for carbide slag is as follows: 3Ca(OH)2+2H3PO4→Ca3(PO4)2↓+6H2O3Ca(OH)2+2H3PO4→Ca3(PO4)2↓+6H2O Ca(OH)2+2HF→CaF2↓+2H2OCa(OH)2+2HF→CaF2↓+2H2O The calcium phosphate (Ca3(PO4)2) and calcium fluoride (CaF2) precipitates generated by the above reaction have good chemical stability and do not participate in subsequent hydration and carbonization reactions. Instead, they are dispersed in the slurry in the form of fine crystals, playing the role of filling micro-aggregates.
[0037] In step 4, foam is produced using a foaming machine and a high-ratio anionic surfactant-type foaming agent. The foaming pressure should be strictly controlled within the range of 100~160 kPa; in this embodiment, 130 kPa is preferred. The foam dry density is controlled between 40~60 kg / m³. 3Within a certain range, the bubble size is controlled within the range of 5~200µm, with the pore size of the main bubble group distributed between 50~150µm. This pore size range is determined based on the following technical considerations: when the pore size is too small (e.g., less than 5µm) or the connectivity between bubbles is too low, the diffusion resistance of CO2 gas in the pores increases sharply, making it difficult for gas molecules to fully dissolve in the pore liquid and penetrate deeper, resulting in insufficient internal mineralization reactions; when the pore size is too large (e.g., greater than 200µm), although the gas permeation resistance decreases, large pores become stress concentration sources, significantly weakening the macroscopic load-bearing capacity and flexural strength of the material. Experimental data show that foam prepared within a foaming pressure range of 100~160kPa has bubble diameters mainly distributed in the range of 50~150µm, with bubble wall thicknesses of approximately 1~5µm. The foam exhibits a uniform, closed, and porous structure, ensuring both rapid CO2 gas permeation and diffusion while maintaining the structural stability of the foam in the slurry.
[0038] The dilution ratio of the foaming agent is determined based on the type of foaming agent and the target foaming ratio. Typically, the foaming agent concentrate is diluted 30-50 times with water before foaming, achieving a foaming ratio of 20-40 times. During the foaming process, a high-speed rotating impeller continuously draws air into the liquid. Under the action of surfactant molecules, the air is broken into numerous tiny bubbles, which are then encapsulated by a liquid film formed by the surfactant molecules. The stability of the foam depends on the surface tension and viscosity of the liquid film. The double-layer structure formed on the bubble surface by anionic surfactants effectively prevents bubble coalescence, thus improving foam stability.
[0039] In step 5, the foam prepared in step 4 is added to the gelling slurry obtained in step 3 and mixed at low speed. The stirring speed is controlled at 60~80 rpm, preferably 70 rpm in this embodiment. The stirring time is controlled at 1.5~2.0 minutes, 1.8 minutes in this embodiment. The purpose of low-speed stirring is to minimize foam breakage and loss under mechanical shearing while ensuring uniform foam distribution. Too high a stirring speed will generate strong shear force, and the bubbles will be subjected to excessive shear stress in the liquid film, which will easily lead to bubble coalescence, breakage, and gas escape. Too short a stirring time will result in uneven spatial distribution of foam in the slurry, with local enrichment or absence of areas, affecting the consistency of the pore structure and performance uniformity of the final product.
[0040] The uniformly mixed foamed cementitious slurry is poured into a pre-prepared curbstone mold. This embodiment uses a standard curbstone mold, with internal dimensions conforming to the requirements of the "JC / T899-2016 Concrete Curbstone" standard. The pouring process employs a self-compacting molding process, eliminating the need for additional vibration. Vibration causes foam to rise and aggregate under the force of vibration, disrupting the uniformity of foam distribution. Simultaneously, the vibration force can cause some air bubbles to burst, reducing the foaming effect. Self-compacting molding relies on the slurry's own fluidity and gravity to achieve complete filling of the mold, maintaining the original spatial distribution of the foam within the slurry.
[0041] After casting, the samples are left to stand for initial setting. The initial setting time is determined by the formation of initial structural strength and the ability to lock in air bubbles. Under normal temperature (20~25℃) conditions, the initial setting time is approximately 2~4 hours; under low temperature (5~10℃) conditions, the initial setting time may be extended to 6~8 hours. Before initial setting, the slurry is in a fluid state, and the foam tends to float slightly under buoyancy; after initial setting, the slurry gradually loses its fluidity, and the foam is permanently fixed in its spatial position, forming a stable porous structure. The standing environment should maintain a relative humidity greater than 60% to prevent excessively rapid evaporation of surface moisture, which could lead to cracking.
[0042] In step 6, the first stage of the multi-stage curing process is carbon dioxide carbonization curing. The pre-cured specimens are placed in a sealed carbonization curing chamber or box. The carbonization curing chamber should have good airtightness to ensure no CO2 gas leakage. Industrial-grade carbon dioxide gas or pretreated industrial flue gas (CO2 volume concentration not less than 20%) is introduced; in this embodiment, industrial-grade CO2 gas with a purity of 99.5% or higher is used. The carbonization pressure is strictly controlled within the range of 0.2~0.3 MPa; in this embodiment, it is 0.25 MPa. The carbonization curing time is controlled within the range of 24~48 hours; in this embodiment, it is 36 hours.
[0043] During pressurized carbonization curing, CO2 gas rapidly penetrates into the material's interior through a network of interconnected micropores formed during foaming, driven by pressure. The 5-200 µm micropore network formed during the foaming stage becomes a rapid channel for CO2 gas diffusion, with gas molecules advancing towards the core region of the specimen along these interconnected pores. CO2 gas dissolves in the pore liquid to form carbonic acid (H2CO3), which ionizes to release bicarbonate ions (HCO3-). - ) and hydrogen ions (H + The calcium carbonate undergoes a deep carbonation reaction with excess calcium hydroxide and calcium silicate gel (CSH) produced by hydration in the system, generating nanoscale calcium carbonate crystals in situ. These calcium carbonate crystals firmly adhere to the foam pore walls, forming a dense "nanocrystalline framework," which not only blocks possible capillary leakage channels but also significantly improves the early compressive strength of the material. The core equation for the carbonation reaction is as follows: Ca(OH)2+CO2→CaCO3↓+H2OCa(OH)2+CO2→CaCO3↓+H2O After carbonization curing, the specimens are demolded and enter the second stage of curing. The second stage involves subsequent natural curing or periodic water spraying curing, with curing cycles including 7 days, 14 days, and 28 days. In a standard curing room, the temperature is controlled at 20±2℃, and the relative humidity is greater than 95%. Under outdoor curing conditions, the specimen surface is kept moist by periodic water spraying, 2-3 times per day, each time spraying until a thin water film forms on the surface. The initial carbon dioxide mineralization curing primarily improves early strength and densifies the microstructure, while the later hydration curing ensures the full hydration reaction of the internal cementitious materials, resulting in stable final performance.
[0044] The curbstone prepared by the method in this embodiment has the following performance indicators: apparent density of 1250 kg / m³. 3 Compared to traditional concrete, it reduces weight by more than 40%; its early compressive strength reaches 11.5 MPa after 3 days, which is more than 3.5 times the strength under natural curing conditions; its compressive strength reaches 18.2 MPa after 28 days, fully meeting the mechanical requirements of lightweight / pedestrian curb stones in "JC / T899-2016 Concrete Curb Stones"; its carbonation depth reaches complete carbonization, indicating a significant internal deep mineralization enhancement effect; and its free phosphorus leaching concentration is only 0.05 mg / L, far below the limit specified in "GB5085.3 Hazardous Waste Identification Standard Leaching Toxicity Preliminary Screening", posing no risk of secondary environmental pollution.
[0045] Example 2
[0046] This embodiment adjusts the raw material ratio and process parameters to verify the technical feasibility under high phosphogypsum dosage conditions.
[0047] In step 1, the amount of phosphogypsum is increased to the maximum permissible range. The solid dry material ratio per 100 parts by weight is: 50 parts phosphogypsum, 15 parts mineral powder, 5 parts calcium carbide slag, 15 parts fly ash, and 15 parts manufactured fine sand. The calcium carbide slag content is increased to 5 parts to address the increased free phosphoric acid and fluoride impurities resulting from the higher phosphogypsum content, ensuring sufficient alkaline activation and in-situ passivation. The manufactured fine sand content is reduced to 15 parts to maintain the total solid dry material content at 100 parts while ensuring a higher powder ratio to maintain the cohesiveness of the cementitious slurry.
[0048] The amount of mixing water added is 35% of the total amount of powder (85 parts by weight) after removing the fine sand from the machine, i.e., 29.75 parts by weight. A higher water-cement ratio helps improve the rheological properties of the slurry under high phosphogypsum content conditions, but at the same time, it is necessary to strictly control the amount of foam added to avoid excessive weight loss.
[0049] In step 4, the foaming pressure is increased to 160 kPa to obtain foam with lower density and higher porosity, compensating for the increased system viscosity caused by the high phosphogypsum content. The foamed dry density is controlled at 40~45 kg / m³. 3 Within the specified range, the amount of foam added is increased to 40% of the volume of the gelatinous slurry to achieve a greater weight reduction effect.
[0050] In step 6, the carbonization curing pressure is increased to 0.3 MPa, and the carbonization curing time is extended to 48 hours. This is because a high phosphogypsum content means more calcium hydroxide is available for the carbonization reaction, and more pore spaces need to be filled by calcium carbonate crystals.
[0051] The curbstone prepared by the method in this embodiment has the following performance indicators: apparent density reduced to 1150 kg / m³. 3 Compared with traditional concrete, it reduces weight by more than 48%; the early compressive strength at 3 days reaches 9.8 MPa; the compressive strength at 28 days reaches 15.6 MPa, meeting the mechanical requirements of "JC / T899-2016 Concrete Curbstone"; the carbonation depth reaches complete carbonation, indicating that even under high admixture conditions, CO2 can still penetrate into the core area; the free phosphorus leaching concentration is 0.08 mg / L, which is slightly higher but still far below the standard limit.
[0052] Example 3
[0053] This embodiment uses a lower phosphogypsum content and foaming parameters to prepare high-strength lightweight foamed curb stones.
[0054] In step 1, the raw material proportions per 100 parts by weight are: 40 parts phosphogypsum, 20 parts mineral powder, 3 parts carbide slag, 17 parts fly ash, and 20 parts manufactured fine sand. A lower phosphogypsum content (40 parts) is beneficial for obtaining higher mechanical properties and better durability. The amounts of mineral powder and fly ash are correspondingly increased to compensate for the reduced contribution of cementitious activity due to the decrease in phosphogypsum. The amount of carbide slag is reduced to 3 parts because the impurity content of the phosphogypsum is correspondingly reduced.
[0055] The amount of mixing water was 28 parts by weight, and the water-cement ratio was 0.35, consistent with Example 1.
[0056] In step 4, the foaming process, the foaming pressure is reduced to 100 kPa, and the dry density of the foam is controlled at 55~60 kg / m³. 3 Within the specified range, the amount of foam added is reduced to 20% of the volume of the gelling paste to reduce porosity and increase density, thereby achieving higher mechanical strength.
[0057] In step 6, the carbonization pressure was reduced to 0.2 MPa, and the carbonization time was 36 hours. The lower carbonization pressure was sufficient to meet the CO2 permeation requirements under low porosity conditions.
[0058] The curbstone prepared by the method in this embodiment has the following performance indicators: apparent density of 1350 kg / m³. 3 Compared with traditional concrete, it reduces weight by more than 30%; the early compressive strength reaches 14.2 MPa after 3 days; the compressive strength reaches 21.5 MPa after 28 days, with a significant improvement in strength grade; the carbonization depth reaches complete carbonization; the free phosphorus leaching concentration is only 0.03 mg / L, with the best environmental performance.
[0059] Comparative Example 1 This comparative study verifies the necessity of CO2 mineralization curing over natural air curing. Under the same raw material ratios and process parameters, step 6, the carbonization curing stage, was replaced with natural air curing. During curing, the molded specimens were placed in a standard curing room (temperature 20±2℃, relative humidity greater than 95%) for static curing.
[0060] Experimental results show that the specimen cured by natural air exhibited an early compressive strength of only 3.2 MPa after 3 days, far lower than the 11.5 MPa in Example 1, with a strength increase of only 2.6 times. This result fully demonstrates the irreplaceable role of CO2 mineralization curing in accelerating the early strength development of phosphogypsum-based materials. Under natural curing conditions, the early hydration process of phosphogypsum-based materials is extremely slow, and the amount of CSH gel generated is insufficient to form an effective strength framework; while CO2 mineralization curing can generate a large number of nano-calcium carbonate crystals in the early stage, rapidly establishing strength through the dual effects of crystal nucleation induction and pore filling.
[0061] Comparative Example 2 This comparative study verifies the alkali-activated passivation effect of calcium carbide slag. Under the same raw material ratio, the amount of calcium carbide slag was reduced from 4 parts to 0 parts, and the missing 4 parts of calcium carbide slag were replaced with an equal amount of manufactured fine sand to maintain the total amount of solid dry material unchanged.
[0062] During the experiment, it was found that after removing the carbide slag, the gelling slurry exhibited significant non-coagulation. The slurry remained in a fluid state for 30 minutes after mixing, failing to form an effective gel structure. After demolding, the specimens suffered severe mold collapse and could not maintain their shape. After the 28-day curing period, the specimens were completely unusable and could not be tested for mechanical properties. The free phosphorus leaching concentration in the curing waste liquid and sample fragments was measured to be 15.4 mg / L, far exceeding the standard limit.
[0063] This result fully demonstrates that the strongly alkaline environment provided by carbide slag is the chemical prerequisite for maintaining the system and achieving in-situ passivation. When carbide slag is lacking, the free phosphoric acid and fluorides in phosphogypsum cannot be neutralized, but instead react with the cementitious materials, consuming hydration products, destroying the slurry structure, and leading to system collapse.
[0064] Comparative Example 3 This comparative study verifies the synergistic inventiveness of physical foaming and CO2 mineralization. Under the same raw material ratio and curing conditions (0.25MPa CO2 carbonization curing), the foaming process in steps 4 and 5 is eliminated, and the foam-free gelling slurry is directly poured into the mold.
[0065] Experimental results show that the apparent density of the non-foamed dense specimen is as high as 2100 kg / m³. 3 Compared to traditional concrete, it loses its lightweight advantage. More importantly, its 28-day compressive strength is only 14.5 MPa, even lower than the 18.2 MPa after foaming and weight reduction in Example 1. Carbonation depth testing results show that the CO2 penetration depth is less than 3 mm, indicating that the dense structure severely hinders the internal penetration of CO2 gas. The free phosphorus leaching concentration is 0.65 mg / L, significantly higher than in Example 1.
[0066] This result reveals a deep synergistic relationship between the foaming process and CO2 mineralization curing: the microporous network formed by foaming is not only a means of weight reduction, but also a physical channel for CO2 gas penetration and diffusion; both are indispensable, and only through synergy can the dual goals of deep mineralization enhancement and lightweight high strength be achieved.
[0067] Comparative Example 4 This comparative example verifies the necessity of pressurized carbonization compared to atmospheric pressure carbonization. Under the same raw material ratio and process parameters, the carbonization curing pressure in step 6 was reduced from 0.25 MPa to atmospheric pressure (0.1 MPa), and CO2 gas permeated into the interior of the specimen through natural diffusion.
[0068] Experimental results showed that the carbonization depth of the specimen cured with CO2 at atmospheric pressure was only 15 mm, far lower than the complete carbonization in Example 1. This indicates that under atmospheric pressure, CO2 gas cannot overcome the significant diffusion resistance and is difficult to penetrate into the core area of the specimen. The 28-day compressive strength was 13.4 MPa, a decrease of 26.4% compared to Example 1. The free phosphorus leaching concentration was 0.45 mg / L, an increase of 9 times compared to Example 1.
[0069] This result demonstrates that a pressure of 0.2–0.3 MPa is a key process parameter for achieving deep carbonization. Only under appropriate pressure can CO2 gas rapidly penetrate into the material through the microporous network formed by foaming, achieving a comprehensive and uniform mineralization enhancement effect.
[0070] Alternative Solution 1: Alternatives to Alkali Activators In step 1, the provider of the strong alkaline environment, in addition to the preferred carbide slag, may be one or more combinations of the following substances: quicklime (CaO), steel slag powder, or sodium hydroxide (NaOH).
[0071] Quicklime requires slaking treatment before use. Mix quicklime and water at a mass ratio of 1:3, slake for 1-2 hours, then sieve to remove unslaked particles to obtain slaked lime slurry. Steel slag powder should be selected with a calcium oxide content higher than 50% and a free calcium oxide content lower than 3% to ensure sufficient alkalinity without introducing excessive unstable components. Sodium hydroxide can be directly prepared into an aqueous solution of a certain concentration, but its impact on the hydration kinetics of cementitious materials should be considered, and the curing regime may need to be adjusted appropriately.
[0072] All of the above alternatives can activate mineral powder and fly ash, and passivate free phosphorus and fluorine impurities in situ. However, carbide slag is the best choice because of its wide availability, low cost, and mild alkalinity.
[0073] Alternative Solution 2: Replacement Solutions for Foaming Methods In step 4, in addition to using the physical foaming method (foaming machine + foaming agent), a chemical foaming method can also be used. The principle of chemical foaming is to add an appropriate amount of gas-generating agent to the dry mixture, and generate gas in situ inside the slurry through a chemical reaction, forming a porous structure.
[0074] Commonly used gas-generating agents include hydrogen peroxide (H2O2) and aluminum powder (Al). Hydrogen peroxide decomposes under the action of a catalyst: 2H2O2 → 2H2O + O2↑, releasing oxygen gas. Aluminum powder reacts under alkaline conditions: 2Al + 6H2O → 2Al(OH)3 + 3H2↑, releasing hydrogen gas.
[0075] The advantage of chemical foaming is that the gas generation process occurs simultaneously with the slurry solidification process, and the bubbles are immediately fixed in the hardened slurry, eliminating the problem of foam floating. However, controlling the pore size in chemical foaming is more difficult. The hydrogen peroxide decomposition rate is affected by temperature and catalyst dosage, and the gas generation of aluminum powder is significantly affected by the pH value of the alkaline environment. Therefore, when using chemical foaming, it is necessary to determine the optimal dosage of the gas-generating agent and the type of catalyst through preliminary experiments to ensure that the pore size distribution is controlled within the range of 5~200µm.
[0076] Alternative Solution 3: Replacement for Carbonization Maintenance Gas Source In step 6, besides using high-purity CO2 gas as the gas source for sealed carbonization curing, industrial waste gas can also be directly introduced as the carbonization gas source. Industrial waste gas sources include tail gas from chemical plants, flue gas from thermal power plants, and converter gas from steel smelting. These industrial waste gases typically contain 20% to 40% CO2 by volume, and after pretreatment such as dust removal, desulfurization, and denitrification, they can be directly used for carbonization curing.
[0077] Using industrial waste gas as a carbonization gas source not only reduces the cost of carbonization maintenance but also enables the resource utilization of industrial exhaust gas, resulting in significant economic and environmental benefits. Pretreatment processes require controlling SO2 and NO in the waste gas. x The content of these acidic gases is important because they can react with alkaline substances in the slurry, affecting the mineralization effect.
[0078] Alternative Option 4: Optimization of the Maintenance System In step 6, after carbonization curing is completed and the mold is removed, in addition to traditional natural curing or water spraying curing, accelerated curing methods such as steam curing or immersion curing can also be used.
[0079] Steam curing involves placing the demolded specimens in a steam curing chamber and curing them in a saturated steam environment at 60-80℃ for 24-48 hours. High-temperature steam accelerates the hydration reaction of the cementitious material, allowing the strength to reach over 80% of the design value in a shorter time. Immersion curing involves completely submerging the specimens in water at 20±2℃. Under water curing conditions, all surfaces of the specimens can absorb water evenly, resulting in a more complete hydration reaction.
[0080] This invention organically couples the alkali activation and in-situ impurity passivation effects of carbide slag with the pressurized mineralization enhancement effect of CO2, constructing a complete non-calcined undisturbed phosphogypsum-based lightweight foamed curbstone preparation technology system. The core innovation of this technology system lies in utilizing the interconnected microporous network formed by physical foaming as a diffusion channel for CO2 gas permeation, transforming the foamed pores from traditional "mechanical defects" into "mineralization microreactors," achieving a deep internal mineralization enhancement effect that traditional dense materials cannot reach. Simultaneously, the cement-free design allows for a phosphogypsum content of up to 50%, significantly improving the efficiency of solid waste resource utilization.
[0081] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a non-calcined, unprocessed phosphogypsum-based lightweight foamed curbstone, characterized in that, Includes the following steps: Step 1 Raw material weighing: Each preset number of solid dry materials contains a preset first proportion of phosphogypsum, a preset second proportion of mineral powder, a preset third proportion of carbide slag, a preset fourth proportion of fly ash, and a preset fifth proportion of machine-made fine sand; the phosphogypsum is uncalcined undisturbed phosphogypsum, and the moisture content is controlled within a preset moisture content range; the amount of mixing water is a preset sixth proportion of the total mass of solid dry materials after removing the machine-made sand; the physical foaming agent is diluted with water and pre-prepared into foam by a foaming machine, and added according to a preset seventh proportion; Step 2: Add the phosphogypsum, mineral powder, carbide slag, fly ash and machine-made fine sand prepared in Step 1 into a mixer and mix them dry. Step 3: Add the specified amount of mixing water to the uniformly mixed solid dry material from Step 2 and perform wet mixing. Control the speed within the preset first speed range and stir for the preset first time period until a uniform gel slurry is formed. Step 4: Use a foaming machine and foaming agent to produce foam. The foaming pressure should be controlled within the preset first pressure range, the foam dry density should be controlled within the preset density range, and the bubble size should be controlled within the preset pore size range. Step 5: Add the foam prepared in Step 4 to the gelling slurry prepared in Step 3, stir at low speed until uniform, control the stirring speed within the preset second speed range, stir for the preset second time period, then pour the foam-containing mixture into the mold, self-compact and form, let the formed sample stand, wait for initial setting, form initial structural strength, and lock the air bubbles. Step 6: Place the pre-cured specimen in a sealed carbonization curing chamber or curing box, introduce carbon dioxide or pretreated industrial flue gas, ensure that the carbon dioxide volume concentration is not lower than the preset concentration threshold, and control the pressure within the preset second pressure range, and cure for the preset second time period.
2. The preparation method according to claim 1, characterized in that, In step 1, the phosphogypsum is the untreated phosphogypsum without any high-temperature calcination treatment.
3. The preparation method according to claim 1, characterized in that, In step 1, calcium carbide slag is used as the core activator, and the amount of calcium carbide slag used is controlled within the preset calcium carbide slag usage range.
4. The preparation method according to claim 1, characterized in that, In step 1, mineral powder and fly ash are used as auxiliary cementing materials. The total mass of mineral powder and fly ash is controlled within the preset auxiliary cementing material ratio range. Under the alkaline activation of carbide slag, mineral powder and fly ash undergo a pozzolanic reaction to generate hydrated calcium silicate gel, which together with the subsequently generated calcium carbonate forms a gel-microcrystalline dual network structure.
5. The preparation method according to claim 1, characterized in that, In step 1, the manufactured fine sand is used as micro-aggregate, and the amount used is controlled within the preset fine sand usage range.
6. The preparation method according to claim 1, characterized in that, In step 3, the wet mixing speed is controlled within a preset first speed range, and the mixing time is controlled within a preset first time period.
7. The preparation method according to claim 1, characterized in that, In step 4, the foaming pressure is controlled within a preset first pressure range, the foaming dry density is controlled within a preset density range, and the bubble size is controlled within a preset pore size range.
8. The preparation method according to claim 1, characterized in that, In step 5, the low-speed stirring speed after the foam is added is controlled within a preset second speed range, and the stirring time is controlled within a preset second time period.
9. The preparation method according to claim 1, characterized in that, In step 6, the pressure of carbon dioxide carbonization curing is controlled within a preset second pressure range, the carbon dioxide volume concentration is not lower than a preset concentration threshold, and the curing time is controlled within a preset second time period range.
